Research note on the social and economic life of village people in central Java: A Case Study of Two Villages in Yogyakarta Special Region - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
This is a tentative research note of the field-work which was conducted under the title of "Research Note on the Social and Economic Life of the Village People in Central Java" in two villages in Bantul Regency, Yogyakarta Special Region for the period of one year September 1989 to March 1990. This research aims at finding the Javanese attributes of the social structure of changing village community and social and economic life of the village people. In general the spread effects of economic development and the process of social change in the rural areas are different between the village communities which are near from the cities or distant. To accomplish the research purpose more efficiently, the research study was carried out in the two villages in Bantu' Regency where is one of the typical Javanese and wet rice areas. But, in this note, objectives and methods of the research, general condition of two hamlets, composition of the households, occupations of the households'heads and farm households by owner ship status are covered. These results of the household survey in the two research sites indicate some emerging trends that the effects of economic development is stronger in the village within easy commuting distance to Yogyakarta City and that the attributes of the village people directed to money economy are also stronger there.